89.6k views
2 votes
Its partial differentiation ​

Its partial differentiation ​-example-1

1 Answer

3 votes

It looks like you're supposed to show


u_x+u_y=u

We have


u=(e^(x+y))/(e^x+e^y)

In the numerator, we have
e^(x+y)=e^xe^y, so that the derivative wrt either
x or
y is simply
e^xe^y=e^(x+y). In the denominator, either
e^x or
e^y vanishes.

Differentiating wrt
x gives, by the quotient rule,


u_x=(e^(x+y)(e^x+e^y)-e^(x+y)e^x)/((e^x+e^y)^2)=(e^(x+y)e^y)/((e^x+e^y)^2)

Similarly, differentiating wrt
y gives


u_y=(e^(x+y)e^x)/((e^x+e^y)^2)

Then


u_x+u_y=\frac{e^(x+y)(e^y+e^x)}(e^x+e^y)^2}


u_x+u_y=\frac{e^(x+y)}e^x+e^y}=u

as required.

User Igor Ilic
by
5.2k points